Occupational therapy for physical dysfunction - Dirette, Diane Powers, ....-; Gutman, Sharon A., ....- (S.l. : Wolters Kluwer, 2020)
Designed to help students become effective, reflective practitioners, this fully updated edition of the most widely used occupational therapy text for the course continues to emphasize the &;whys&; as well as the &;how-tos&; of holistic assessment and treatment. Now in striking full color and co-edited by renowned educators and authors Diane Powers Dirette and Sharon Gutman, Occupational Therapy for Physical Dysfunction, Eighth Edition features expert coverage of the latest assessment techniques and most recent trends in clinical practice. In addition, the book now explicitly integrates &;Frames of Reference&; to help students connect theories to practice and features a new six-part organization, thirteen all-new chapters, new pedagogy, and more.
Keywords: Ergotherapie